2017
DOI: 10.1002/acn3.435
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 predicts outcome and hemorrhagic transformation after acute stroke

Abstract: Objective ST2 is a member of the toll‐like receptor superfamily that can alter inflammatory signaling of helper T‐cells. We investigated whether soluble ST2 (sST2) could independently predict outcome and hemorrhagic transformation (HT) in the setting of stroke.MethodsWe measured sST2 in patients enrolled in the Specialized Program of Translational Research in Acute Stroke (SPOTRIAS) network biomarker study. 646 patients had plasma samples collected at the time of hospital admission and 210 patients had a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 36 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…Recently, the high level of serum sST2 has been found to be associated with incident stroke/transient ischemic attack (TIA) [16]. The elevated sST2 has also been shown to be related to worse outcome and higher mortality after AIS [17]. However, the conclusions from another study in a large cohort of AIS patients revealed that serum sST2 may not be a strong and independent prognostic marker for AIS mortality [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the high level of serum sST2 has been found to be associated with incident stroke/transient ischemic attack (TIA) [16]. The elevated sST2 has also been shown to be related to worse outcome and higher mortality after AIS [17]. However, the conclusions from another study in a large cohort of AIS patients revealed that serum sST2 may not be a strong and independent prognostic marker for AIS mortality [18].…”
Section: Introductionmentioning
confidence: 99%
“…17 sST2 acts as a decoy receptor, reducing the interaction of IL-33 with transmembrane ST2 and therefore shifting toward a proinflammatory response. 25,26 We recently identified sST2 as a marker of secondary brain injury and functional neurologic outcome after ischemic stroke, 27 suggesting it may also play a role in the immune response to neurovascular injury. 25,26 We recently identified sST2 as a marker of secondary brain injury and functional neurologic outcome after ischemic stroke, 27 suggesting it may also play a role in the immune response to neurovascular injury.…”
mentioning
confidence: 99%
“…In cerebrovascular disease, prior work found that sST2 is an independent predictor for poor functional outcomes (mRS>2) 3 months after AIS [8,9]. Additionally, sST2 levels were found to independently correlate with 90-day mortality and hemorrhagic transformation after AIS [9]. However, the predictive value of sST2 for all-cause mortality 90 days after ischemic stroke showed no statistical significance after multivariate adjustment [10].…”
Section: Discussionmentioning
confidence: 98%
“…sST2 is a prognostic marker in patients with heart failure and myocardial infarction [24,25] and significantly associated with incident stroke/TIA in previously stroke-free individuals [7]. In cerebrovascular disease, prior work found that sST2 is an independent predictor for poor functional outcomes (mRS>2) 3 months after AIS [8,9]. Additionally, sST2 levels were found to independently correlate with 90-day mortality and hemorrhagic transformation after AIS [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation